RELATIONSHIP BETWEEN DIABETES SELF CARE MANAGEMENT AND DIABETIC PERIPHERAL NEUROPATHY IN ELDERLY PEOPLE WITH DIABETES MELLITUS IN JEMBER REGENCY - Yoga Bagus Santoso Putra; Trisna Vitaliati; Nurul Maurida (UPT Penerbitan Universitas Jember, 2023)
Background: Around the world, 66% of people with diabetes mellitus have diabetic peripheral neuropathy (DPN). DPN is a major cause of morbidity and mortality due to complications such as diabetic foot ulcers, which often result in amputation of extremities or difficulty maintaining balance which results in trauma. DPN is nerve damage caused by hyperglycemia. DM patients who are able to manage their disease independently such as controlling blood sugar is called diabetes self care management (DSCM). Objective: To analyze the relationship between diabetes self care management and diabetic peripheral neuropathy in elderly people with diabetes mellitus in Jember Regency. Methods: This research is an observational study with a cross-sectional design with a purposive sampling technique to determine which Community Health Centers in Jember Regency will be used as research sites. The number of samples is 101 elderly with diabetes mellitus in Jember Regency. The DSCM data collection used The Summary of Diabetes Self Care Activities Questionnaire and the DPN used the Neuropathy System Score. Results: The level of diabetes self care management in elderly DM in Jember Regency was in the poor category, with the majority being 61 people (60.4%). The level of diabetic peripheral in the elderly with diabetes mellitus in Jember Regency is in the severe category, with 67 people (66.3%). In the Pearson correlation test, the relationship between diabetes self care management and diabetic peripheral neuropathy in elderly people with diabetes mellitus in Jember Regency obtained a p-value of 0.000 (p <0.05). Discussion: The better the DSCM score, the lighter the DPN complications and vice versa. Conclusion: There is a relationship between diabetes self care management and diabetic peripheral neuropathy in elderly people with diabetes mellitus in Jember Regency. Keywords: Diabetic Peripheral Neuropathy, Self Care Management, Diabetes Mellitus, Elderly